2017
DOI: 10.1016/j.onehlt.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

The hookworm Ancylostoma ceylanicum : An emerging public health risk in Australian tropical rainforests and Indigenous communities

Abstract: Ancylostoma ceylanicum is the common hookworm of domestic dogs and cats throughout Asia, and is an emerging but little understood public health risk in tropical northern Australia. We investigated the prevalence of A. ceylanicum in soil and free-ranging domestic dogs at six rainforest locations in Far North Queensland that are Indigenous Australian communities and popular tourist attractions within the Wet Tropics World Heritage Area. By combining PCR-based techniques with traditional methods of hookworm speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 19 publications
(29 reference statements)
0
37
1
Order By: Relevance
“…Moreover, A. ceylanicum is the only zoonotic hookworm known to produce patent intestinal infections in humans. More recently, a number of studies have been reported looking at molecular diagnosis of zoonotic A. ceylanicum in humans and dogs in different parts of the world [ 72 77 ]. Despite A. caninum being the most widely distributed among hookworms, it infrequently causes eosinophilic enteritis in humans [ 78 ].…”
Section: Trends Of Probiotics Against Helminth Zoonosismentioning
confidence: 99%
“…Moreover, A. ceylanicum is the only zoonotic hookworm known to produce patent intestinal infections in humans. More recently, a number of studies have been reported looking at molecular diagnosis of zoonotic A. ceylanicum in humans and dogs in different parts of the world [ 72 77 ]. Despite A. caninum being the most widely distributed among hookworms, it infrequently causes eosinophilic enteritis in humans [ 78 ].…”
Section: Trends Of Probiotics Against Helminth Zoonosismentioning
confidence: 99%
“…The risk of zoonotic transmission increases when dogs and cats are kept at high population densities in association with humans [ 2 ], such as in RACs. Sarcoptic mange ( Sarcoptes scabiei ), hookworm ( Ancylostoma caninum ), fleas, ticks ( Rhipicephalus sanguineus ), and giardia ( Giardia duodenalis ) have all been documented in dogs in RACs [ 3 , 4 , 5 , 6 ]. Limited research conducted on cats in Aboriginal communities has identified tapeworm ( Spirometra erinacei ), Oncicola spp., hookworm ( Ancylostoma caninum ), and Toxoplasma gondii in cats in Northern Australia [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Domestic animals can also impact native wildlife. Globally, FRDs threaten wildlife conservation through predation [ 7 , 8 , 9 ], disturbance [ 10 , 11 , 12 ], competition [ 13 , 14 ], and disease transmission [ 3 , 4 , 6 , 15 , 16 ]. Cats primarily impact wildlife through direct predation, but also competition and disease transmission [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, A. caninum was also sporadically reported to cause eosinophilic enteritis because its larvae can develop into pre-adult, non-patent worms in human intestines (Landmann and Prociv 2003). Recent increased molecular-based epidemiological evidence highlights that A. caninum and A. ceylanicum are emerging as important helminthic zoonosis in the Asia Pacific countries including Cambodia (Inpankaew et al 2014), Laos (Sato et al 2010), Malaysia (Ngui et al 2012), Solomon Islands (Bradbury et al 2017), Thailand (Jiraanankul et al 2011), Australia (Smout et al 2017) and China (Dai et al 2009;Liu et al 2013). However, current diagnosis of this zoonotic infection is still largely based on faecal microscopy and often misdiagnosed even by experienced microscopists due to the inability to morphologically distinguish A. caninum eggs from those of other hookworms (Monis et al 2002).…”
mentioning
confidence: 99%